Pengaruh Ketinggian Tempat dan Curah Hujan Pada Penyakit Diare (Studi Kasus: Kabupaten Bogor) - Muhammad Syafei; Rini Hidayati (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2014)
This study aimed to determine the effect of altitude and rainfall on the incidence of disease ( IR ) diarrhea, and to obtain threshold values of rainfall that often cause diarrhea. Determination category of normal rate of diarrhea IR is based on diarrhea IR by DINKES Bogor in the amount of 20-25/1000 population per year, while the determination of precipitation category is based on consideration of Oldeman climate classification. The results showed that there were two districts with very high levels of vulnerability i.e. Cisarua and Cijeruk, while the other regions only at a moderate level. The negative influence of altitude (or positive influence of temperature) on the IR will be evident if the analysis is separated between in the highlands (> 600 asl) and the lowlands (< 600 asl). This influence is significant, especially at altitudes above 600 meters above sea level. The correlation of the precipitation is significant negative linear to the incidence of diarrhea in the district Cisarua, Cibinong, Jonggol, and Jasinga. In districts Cibinong, Jonggol, and Jasinga, precipitation should be anticipated in the range of 100-200 mm/month, where moderate IR often occurs, while in the district Cisarua, is in the range of precipitation 300-400 mm/month, where high IR often occurs.